First record of bilateral hypertrophy in chelas of Uca rapax male specimen (Crustacea, Decapoda, Ocypodidae) on the Brazilian coastline - Vale, Valéria Fonsêca; Alencar, Carlos Eduardo Rocha Duarte; Moraes, Sávio Arcanjo Santos Nascimento; Freire, Fúlvio Aurélio Morais [UNESP] (Cambridge University Press (CUP), 2015)
An adult male specimen of Uca rapax (Crustacea, Decapoda, Ocypodidae), containing bilaterally hypertrophied chelipeds, was found in the mangrove area of the Rio Grande do Norte state, north-eastern Brazil. The chelipeds are subequal in size and similar to the major cheliped of normal male specimens of Uca rapax. This paper is the first record of the aforementioned anomaly for the species from the Brazilian coastline.
Keywords: anomaly; fiddler crabs; super-males; symmetry